THE ILLITERACY IN BRAZIL: LESSONS FROM HISTORY - Braga, Ana Carolina [UNESP]; Carvalho Mazzeu, Francisco Jose [UNESP] (Unesp-faculdade Ciencias & Letras, 2017)
The article discusses the problem of illiteracy in Brazil, seeking to reveal their historical and social roots. It starts from an analysis of the data that leaves an optimistic reading on the gradual fall of the indices. Neither can the fall be considered significant, when one observes the absolute number of illiterates and the trends of the historical series of data, nor is possible attribute this reduction to the results of the public policies. By making a historical study, one can see that economic, political and social relations end up determining the conditions in which the supply of schooling will take place, what persons will have access to it, what will be its possibility of progress, among other aspects. At the same time, educational structures have been at the mercy of the social and economic context, failing to seek an organization that could offers real development opportunities to all students.
Keywords: Illiteracy; Literacy; Literacy Public Policies